Pengembangan Modul Pembelajaran Berbasis Model Creative Problem Solving (CPS) pada Mata Pelajaran Instalasi Peneragan Listrik di SMK Negeri 1 Driyorejo - Alifia Pasa Afryliyani; Joko Joko (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Education plays a crucial and essential role in improving the quality of human resource globally, thus a research was conducted with the aim of producing a product, namely a learning module. This module is one of the learning resources that can be used by students independently. Therefore, the module was developed to function as a learniing guide for students. The lerning model used in this research is Creative Problem Solving. In this learning model, the teacher presents problems so that students can find answers innovatively and sharpen their critical thinking skills. The suitability of this learning module will be evaluated based on three aspect, namely validity, practicality, and effectiveness. Based on the research sample data, this consists of students from class XI Electrical Power Installation Techniques (TITL) 1 at SMKN 1 Driyorejo. This method uses the Research & Development (R&D) approach. The analysis of differences in learning outcomes was carried out using the One Group Pretest-Posttest Method, the treatment in the form of a learning module based on the Creative Problem Solving model was given to student. The research result show that (1) the modules suitability is stated as very valid wth a score of 89,60, (2) aspect, it is stataed as very practical with a total average reaching 90,60, (3) effectiveness is proven from the improvement in learning outcomes in terms of knowledge and domains with an average pretest score of 51,3, while the average posttest score is 85 with a significance of 0.000.